The Development of Cultural Ecotourism-Based Tourism: The Role of Village Governments in Managing Sustainable Tourism in Badung Regency - Lukman, Juwita Pratiwi; Yudartha, I Putu Dharmanu; ktaviani, Kadek Chyntia; Dewi, Ni Putu Diah Sintya; Widiyanti, Selvia; Adristari, Talitha Purnama (Universitas Pattimura, 2025)
This study aims to describe the role of village governments in the development of cultural ecotourism-based tourism by examining four key tourism components: attractions, supporting facilities, accessibility, and additional services. A qualitative approach was employed, using observation and in-depth interviews as data collection techniques, focusing on Abiansemal Village, Badung Regency. The findings reveal that Abiansemal Village offers main attractions such as jogging trails with natural rice field panoramas, historic traditional bathing facilities, and the Melasti Site for self-purification rituals. However, supporting facilities in the village still require development to enhance tourist comfort. Accessibility to destinations is relatively adequate, but additional services, such as the involvement of investors and community elements, need improvement to ensure tourism sustainability. This study highlights the importance of collaboration between village governments, local communities, and private sectors in managing cultural ecotourism-based tourism. As a novel contribution, this research provides insights into how village governments can play a strategic role in managing sustainable tourism at the local level. Recommendations include strengthening infrastructure, enhancing local community capacity, and implementing collaborative strategies to support the development of social sciences and humanities in the context of sustainable tourism.